ISLAM AND MODERN POLITICS: THE IMPACT OF ISLAM ON DEMOCRATIC VALUES AND SYSTEMS - Zokirova Ra’no Islom qizi (Bright Mind Publishing, 2025)
This article analyzes the links between Islam and contemporary politics. The influence of Islam on democratic values and systems, its political, social and moral principles are considered. The topics of the inextricably linked relationship between Islam and democracy, the adoption and development of democracy in Islamic societies are discussed. It also analyzes the influence of Islam on political systems and how it reflects democratic values.
Keywords: Islam, politics, democracy, Islamic values, political systems, society, democratic rights